New Mouride movements in Dakar and the diaspora - Kingsbury, KA (2014)
This thesis looks at two Mouride orders that became very popular among young people in Senegal starting in the year 2000. It focuses not only on the leaders of these two movements, known as marabouts or cheikhs, in Dakar, Senegal, but in particular on their followers, the talibés. The thesis examines the 'Thiantistes', followers of Cheikh Bethio Thioune and at the disciples of Serigne Modou Kara in order to understand why these new Mouride movements, which differ from those that have preceded them, have proven so popular with youth in Dakar. I argue that marginalised youth have impelled the creation of a new form of Sufism in Senegal, in a context whereby they are excluded from the post-colonial state and must navigate numerous difficulties daily, including violence, unemployment, and inability to attain adult status due to severe economic and political limitations. I compare and contrast the new religious movements these youth have created with those that Senegalese migrants in Belgium and France have generated, where racism and other types of exclusion lead to the desire to establish nourishing spiritual networks.